2023
DOI: 10.3390/antiox12081545
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide-Releasing Indomethacin-Derivative (ATB-344) Prevents the Development of Oxidative Gastric Mucosal Injuries

Abstract: Hydrogen sulfide (H2S) emerged recently as an anti-oxidative signaling molecule that contributes to gastrointestinal (GI) mucosal defense and repair. Indomethacin belongs to the class of non-steroidal anti-inflammatory drugs (NSAIDs) and is used as an effective intervention in the treatment of gout- or osteoarthritis-related inflammation. However, its clinical use is strongly limited since indomethacin inhibits gastric mucosal prostaglandin (PG) biosynthesis, predisposing to or even inducing ulcerogenesis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…AP39, a mitochondria-targeted H2S donor, has been employed to treat myocardial I/R injury [31]. ATB-344, a derivative of indomethacin that releases H2S, enhances the gastric mucosa's defense against gastric I/R damage and releases H2S in a dose-dependent manner [16].…”
Section: H2s Donors In I/r Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…AP39, a mitochondria-targeted H2S donor, has been employed to treat myocardial I/R injury [31]. ATB-344, a derivative of indomethacin that releases H2S, enhances the gastric mucosa's defense against gastric I/R damage and releases H2S in a dose-dependent manner [16].…”
Section: H2s Donors In I/r Injurymentioning
confidence: 99%
“…Lack of SOD-2 in mitochondria elevates ROS generation, disrupting the mitochondrial metabolism and cellular redox balance [166]. Gowacka et al [16] found that ATB-344, an indomethacin derivative and novel H2S-releasing drug, significantly reduced gastric lesion size in rats with gastric I/R injury. The ATB-344 treatment group showed reduced 8-amino-3,6-dioxaoctanoic acid (PEG2) and cyclooxygenase-2 (COX-2) levels in the gastric mucosa compared to the I/R group and increased SOD-2 levels while decreasing xanthine dehydrogenase (XDH) and inflammation markers.…”
Section: H2s and Gastric I/r Injurymentioning
confidence: 99%
See 1 more Smart Citation